Pseudorapidity densities of charged particles with transverse momentum thresholds in pp collisions at √s=5.02 and 13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kim, Minjung; Kroesen, Martin; et al. (Physical review, 2023)
The pseudorapidity density of charged particles with minimum transverse momentum (𝑝T) thresholds of 0.15, 0.5, 1, and 2 GeV/𝑐 is measured in pp collisions at the center of mass energies of √𝑠 =5.02 and 13 TeV with the ALICE detector. The study is carried out for inelastic collisions with at least one primary charged particle having a pseudorapidity (𝜂) within ±0.8 and 𝑝T larger than the corresponding threshold. In addition, measurements without 𝑝T-thresholds are performed for inelastic and nonsingle-diffractive events as well as for inelastic events with at least one charged particle having |𝜂| <1 in pp collisions at √𝑠 =5.02 TeV for the first time at the LHC. These measurements are compared to the pythia 6, pythia 8, and epos-lhc models. In general, the models describe the 𝜂 dependence of particle production well. However, discrepancies are observed for the highest transverse momentum threshold (𝑝T >2 GeV/𝑐), highlighting the importance of such measurements for tuning event generators. The new measurements agree within uncertainties with results from the ATLAS and CMS experiments obtained at √𝑠 =13 TeV.